KONSEP NARATIF DALAM FILM DOKUMENTER PEKAK KUKURUYUK - Emilika Budi Lestari (Jurnal Nawala Visual, 2019)
Documentary movie that present reality in various ways and are made for various purposes. Social, political and cultural life mostly inspiresthe documentary. The concept of documentary movie is to build a storyline based on the reality. Documentary movie are made according to certain versions based on the reality. Various techniques can be used to convey information and convince the audience about the situation and conditions in the movie. Unlike fiction films that have a clear narrative structure, documentary films do not have a narrative structure. The main key to a documentary is the presentation of facts. Documentary films relate to real people, figures, events and locations. The style of storytelling in documentaries is non-narrative because documentaries do not contain the composition of the stories in them. In the documentary film Pekak Kukuruyuk, it can be seen that the narrative concept that was built from this film is the concept of realism (real), which is to build a storyline based on reality. Where this concept is opposite to experimental films that have the concept of formalism (abstract). This film was made through a direct recording method when the event actually took place and inserted several reconstructions and interviews in it.